Validation of a Double-Sandwich Enzyme-Linked Immunoassay for Pharmacokinetic Study of an rh-aFGF Hydrogel in Rat Skin and Serum - Hui, Qi; Yang, Rongshuai; Lu, Chao; Bi, Jianing; Li, Lijia; Gong, Jianxiang; Zhang, Li; Jin, Zi; Li, Xiaokun; Wang, Xiaojie (Frontiers in Pharmacology, 2020)
In this study, we validated a double-sandwich enzyme-linked immunosorbent assay (ELISA) to investigate the pharmacokinetics of a recombinant human acidic fibroblast growth factor (rh-aFGF) hydrogel in rat skin and serum. A total of 130 Sprague-Dawley rats were divided into a control group, rh-aFGF hydrogel group, and a positive-control group (commercial rh-aFGF-Ai). We first determined the dilution ratio of skin homogenate and then validated the quantitative range, specificity, precision, and accuracy of our double-sandwich ELISA method, as well as the stability of our rh-aFGF hydrogel. For our pharmacokinetic study, skin and serum samples were collected at 0.5, 1, 2, 4, 6, and 10 h after rh-aFGF administration, and the concentration of rh-aFGF was measured by ELISA. The results showed that a 10-fold dilution of the skin tissue homogenate circumvented non-specific interference with endogenous proteins. The quantitative scope of the rh-aFGF calibration curve ranged from 62.5 to 4,000 pg/mL. The precision and accuracy of rh-aFGF quality-control samples were below 20%. Furthermore, bFGF, FGF21, KGF-2, and insulin did not interfere with the detection of aFGF, confirming that our method was specific. Rh-aFGF was stable under normal storage conditions. The maximum concentration (Cmax) and time to peak (Tmax) of the rh-aFGF hydrogel were 909.2 pg/cm2 and 0.5 h, respectively. The relative bioavailability (F) of the rh-aFGF hydrogel was 120% compared with that of rh-aFGF-Ai. The serum concentration of rh-aFGF was too low to be detected. Taken together, the pharmacokinetics of this rh-aFGF hydrogel provide further support for clinical research on rh-aFGF, and our double-sandwich ELISA method may be useful for pharmacokinetic studies of other protein-based drugs.